Legal Services and Marketing Limitations: A Focus on SME in Malaysia - Abdullah, A.; Kamarulzaman, Y.; Farinda, A.G. (Zia World Press, Australia, Australia, 2008)
There are some jurisdictions in Malaysia that have extensive prohibitions against legal firms' marketing activities, particularly in advertising legal services. Eventually, the jurisdictions pose some limitations to the SMEs in their attempts to expand their businesses, particularly in the practice of legal firms in Malaysia. This study explores the limitations faced by SME legal practitioners especially in the area of marketing of their services. The study also visits the areas in services marketing that are able to accommodate the regulations in the present state. Finally, the study contributes to some suggestions on possible approaches for legal practitioners in exploiting marketing tools and techniques for their business success.